Colors Shapes and More (Grand Haven, Mich School Zone Interactive, 2004)
Makes Learning Child's Play! exercises teach numbers colors shapes positional and rhyming words. 4 creative play centers reinforce concepts. unique design promotes self paced learning
Ages 3-up
System requirements for Windows: Pentium or faster ; Windows 95, 98 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 16-bit sound card ; 4X CD-ROM drive. System requirements for Macintosh: PowerPC 601 or faster processor ; System 7.5.5 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 4X CD-ROM drive
1
Keywords: games -- audiovisual; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs